Uncooled infrared imaging arrays and systems - Kruse, Paul W.; Skatrud, David Dale, 1956- (Semiconductors and semimetals, 1997)
This is the first book to describe an emerging but already growing technology of thermal imaging based on uncooled infrared imaging arrays and systems, which are the most exciting new developments in infrared technology today. This technology is of great importance to developers and users of thermal images for military and commercial applications. The chapters, prepared by world leaders in the technology, describe not only the mainstream efforts, but also exciting new approaches and fundamental limits applicable to all. Key Features * Unified approach to technology development based on fundamental limits * Individual chapters written by world leaders in each technology * Novel potential approaches, allowing for the reduction of costs, described in detail * Descriptive and analytical * Provides details of the mainstream approaches--resistive bolometric, pyroelectric/field enhanced pyroelectric, thermoelectric * Provides insight into a unified approach to development of all types of thermal imaging arrays Features state-of-the-art and selected new developments.